Pengaruh Konseling Realita untuk Menurunkan kecanduan terhadap smartphone dan meningkatkan Prestasi belajar - Finsensius Ratuaki; I Ketut Gading; Ni Ketut Suarni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This article aims to describe the results of research on the effect of reality counseling on reducing smartphone addiction and increasing student achievement in Class VIII SMP. The method used in this study uses the Experiment method. Respondents in this study amounted to 102 students of class VIII SMP Sila Dharma and used the Pretest-Posttest Control Group design and the sample was taken using a purposive random sampling technique. data that has been collected and analyzed using the SPSS 17.0 application for Windows. The results of data analysis show that the Reality Counseling Approach can reduce smartphone addiction and can increase learning achievement and reality counseling can influence simultaneously in reducing smartphone addiction and increasing student learning achievement. after controlling behavior control This article suggests teachers to be able to use the Real Counseling Approach in dealing with student problems, namely reducing smartphone addiction and also to increase student achievement. And also this article suggests that teachers pay more attention to students' smartphone playing habits at school so they can get used to controlling themselves in playing smartphones and teachers are more active in guiding students in the cognitive, affective and psychomotor domains so they can excel in their learning.